Beberapa Permasalahan Arsitektural Pura Sakenan â Bali Pasca Reklamasi Pulau Serangan - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Kedokteran Gigi UGM, 2002)
ABSTRAK Sakenan Temple on Serangan Island, Bali, is under pressure from the significant volume of visitors resulting from the reclamation of Serangan Island in 1996/1997. A Dangkahyangan temple, Sakenan Temple is the second most sacred temple in the Balinese-Hindu religion after Besakih Temple. The volume of visitors has expanded to exceed the capacity of the site of worship, particularly during the celebration of Piodalan. The environmental and behavioural architectural problems are discussed in this paper, in an effort to seek an alternative solution. Because visitors to the temple feel crowded and a lack of privacy, the special meaning of their worship is lost, which ultimately severely undermines the sacred and monumental nature of Sakenan Temple. Organising the space based on the Balinese hierarchical order (Sangamandala) is one possible way of resolving the architectural problems of Sakenan Temple, Bali Keywords: Arsitektural Bali, reklamasi